Risk prediction of in-stent restenosis among patients with coronary drug-eluting stents: current clinical approaches and challenges. (2nd September 2021) - Sakamoto, Atsushi; Sato, Yu; Kawakami, Rika; Cornelissen, Anne; Mori, Masayuki; Kawai, Kenji; Fernandez, Raquel; Fuller, Daniela; Gadhoke, Neel; Guo, Liang; Romero, Maria E.; Kolodgie, Frank D.; et al.
ABSTRACT: Introduction : In-stent restenosis (ISR) has been one of the biggest limitations to the success of percutaneous coronary intervention for the treatment of coronary artery disease (CAD). The introduction of drug-eluting stent (DES) was a revolution in the treatment of CAD because these devices drastically reduced ISR to very low levels (<5%). Subsequently, newer generation DES treatments have overcome the drawbacks of first-generation DES, i.e. delayed endothelialization, and late stent thrombosis. However, the issue of late ISR, including neoatherosclerosis after DES implantation especially in high-risk patients and complex lesions, still exists as a challenge to be overcome. Areas covered : We discuss the mechanisms of ISR development including neoatherosclerosis, past and current clinical status of ISR, and methods to predict and overcome this issue from pathological and clinical points of view. Expert opinion : The initial drawbacks of first-generation DES, such as delayed endothelial healing and subsequent risk of late stent thrombosis, have been improved upon by the current generation DES. To achieve better long-term clinical outcomes, further titration of drug-release and polymer degradation profile, strut thickness as well as material innovation are needed.